Sistem Pakar Untuk Mendiagnosis Penyakit Obsessive Compulsive Disorder (OCD) Dengan Metode Certainty Factor Pada Kimia Farma Rantauprapat - Rambe, Ade Nopriansyah; Dalimunthe, Abdul Hakim; Ulya, Basyarul (U-NET Jurnal Teknik Informatika, 2024)
Anxiety is a normal reaction to stress and can be beneficial in some situations. They can alert us to danger and help us be prepared and pay attention. Anxiety disorders are different from normal feelings of nervousness or anxiety, and involve excessive fear or anxiety. Anxiety disorders can cause people to try to avoid situations that trigger or worsen their symptoms. There are several types of anxiety disorders, inclObsessive Compulsive Disorder. Obsessive Compulsive Disorder (OCD) is a disorder in which people have repeated unwanted thoughts, ideas, or sensations (obsessions) that make them feel compelled to do something repeatedly (compulsions). Repetitive behaviors, such as hand washing, checking items, or cleaning, can significantly interfere with a person's daily activities and social interactions. Expert System that applies the MethodCertainty Factor this can help anyone to ensure that they have OCD and need the help of a psychologist to prevent this disorder from getting worse.